Barriers and opportunities to increase PD incidence and prevalence: Lessons from a European Survey. Issue 6 (November 2021) - Hahn Lundström, Ulrika; Abrahams, Alferso C; Allen, Jennifer; Altabas, Karmela; Béchade, Clémence; Burkhalter, Felix; Clause, Anne-Lorraine; Corbett, Richard W; Eden, Gabriele; François, Karlien; de Laforcade, Louis; Lambie, Mark; et al.
Introduction: Peritoneal dialysis (PD) remains underutilised and unplanned start of dialysis further diminishes the likelihood of patients starting on PD, although outcomes are equal to haemodialysis (HD). Methods: A survey was sent to members of EuroPD and regional societies presenting a case vignette of a 48-year-old woman not previously known to the nephrology department and who arrives at the emergency department with established end-stage kidney disease (unplanned start), asking which dialysis modality would most likely be chosen at their respective centre. We assessed associations between the modality choices for this case vignette and centre characteristics and PD-related practices. Results: Of 575 respondents, 32.8%, 32.2% and 35.0% indicated they would start unplanned PD, unplanned HD or unplanned HD with intention to educate patient on PD later, respectively. Likelihood for unplanned start of PD was only associated with quality of structure of the pre-dialysis program. Structure of pre-dialysis education program, PD program in general, likelihood to provide education on PD to unplanned starters, good collaboration with the PD access team and taking initiatives to enhance home-based therapies increased the likelihood unplanned patients would end up on PD. Conclusions: Well-structured pre-dialysis education on PD as a modality, good connections to dedicated PD catheter placement teams and additional initiatives to enhance home-based therapies are key to grow PD programs. Centres motivated to grow their PD programs seem to find solutions to do so.